GRAND DESIGN PERENCANAAN PEMBANGUNAN EKONOMI BERBASIS EKONOMI KERAKYATAN DALAM UPAYA MENCAPAI PEMBANGUNAN BERKELANJUTAN DI KABUPATEN MALANG - Prasetyia, Ferry; Wulandari, Farah (Journal of Indonesian Applied Economics, 2009)
The objective of  this  research  is  to analyse  the possibility of community economybased (ekonomi kerakyatan) implementation in Malang district in order to achievesustainable economic development. This reseach state that there are four stages incommunity economy based design:  first, mapping the leading economic sectors inMalang District.  Second, mapping  of  socio-political  conditions  surrounding  thecommunity.  Third,  identify  the  existing  institutional  order.  Fourth,  designing  anappropriate form of partnership in order to accommodate the common good of thegovernment, private sector, and society.Keywords: community economy based, partnership, Malang district.